Retirement planning behaviour / Nur Farahin Allia Abdul Nasir - Abdul Nasir, Nur Farahin Allia (Faculty of Business and Management, 2017)
Retirement is a stage that a person stops employment completely. Retirement life need a proper preparation because it can lead a person continuous employment at retirement age. Lack of retirement planning preparation will make them suffer. According to The Ant Daily (29th January 2015), it states that most Malaysians are ill-prepared for life after retirement. Thus, it is very important to have retirement planning. The main aim for this research is to investigate factor affecting retirement planning behaviour among working individuals. For this research, retirement planning behaviour is a dependent variable while attitude toward retirement, potential conflict in retirement and goal clarity are independent variables. For this research, questionnaires will be distributed to 150 working individuals which are limited for age from 26 to 55 years in Tanjung Malim, Perak.